2021
DOI: 10.3390/antiox10060952
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hydrogen Peroxide on Protein Synthesis in Yeast

Abstract: Cells must be able to respond and adapt to different stress conditions to maintain normal function. A common response to stress is the global inhibition of protein synthesis. Protein synthesis is an expensive process consuming much of the cell’s energy. Consequently, it must be tightly regulated to conserve resources. One of these stress conditions is oxidative stress, resulting from the accumulation of reactive oxygen species (ROS) mainly produced by the mitochondria but also by other intracellular sources. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 90 publications
0
11
0
Order By: Relevance
“…This suggests that other cellular inputs contribute to eIF2 phosphorylation in addition to Rad6-mediated redox pausing and these other inputs could be more dominant in the S288C strain. Consistent with this idea that ISR regulation may vary somewhat between strains, it has been reported that Gcn4 translation is not activated by peroxide in the S288C strain (Picazo and Molin, 2021). In addition, S288C has a unique genetic background that affects mitochondria physiology and cellular redox biology (Young and Court, 2008), which could influence redox experiments in this strain.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…This suggests that other cellular inputs contribute to eIF2 phosphorylation in addition to Rad6-mediated redox pausing and these other inputs could be more dominant in the S288C strain. Consistent with this idea that ISR regulation may vary somewhat between strains, it has been reported that Gcn4 translation is not activated by peroxide in the S288C strain (Picazo and Molin, 2021). In addition, S288C has a unique genetic background that affects mitochondria physiology and cellular redox biology (Young and Court, 2008), which could influence redox experiments in this strain.…”
Section: Discussionmentioning
confidence: 66%
“…Cellular stress caused by the accumulation of reactive oxygen species (ROS) affects important biomolecules such as nucleic acids, proteins, and lipids, and is associated with several pathologies, such as cancer, and cardiovascular and neurodegenerative diseases (Finkel and Holbrook, 2000; Liguori et al, 2018; Sharifi-Rad et al, 2020). ROS, including hydrogen peroxide (H 2 O 2 ), can form as a result of metabolic processes but also from exposure to a range of chemicals and pollutants (Picazo and Molin, 2021; Sharifi-Rad et al, 2020). Thus, oxidative stress occurs when ROS production overloads the cellular antioxidant defense.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Redox signaling is a fundamental biological process essential for the maintenance of physiological homeostasis and cell survival, especially under stress conditions. Cellular response to ROS stress has been an important area of study by many laboratories, which have collectively gained significant new insights into the regulatory mechanisms and therapeutic implications [5,[27][28][29]. Although various aspects of redox signaling by H 2 O 2 have been reported in the literature, the impacts of H 2 O 2 on global transcription of mRNA and lncRNA in normal and cancer cells and the respective mechanisms remain to be characterized in detail.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern is indicative of a residue that has been evolutionarily conserved to sense and react to an oxidative stressor. The reversibility of cysteine modification is especially useful as a signal, as it allows for chaperones that contain them to switch between conformations that may have different purposes, with the additional involvement of redox management systems such as the thioredoxin and glutathione pathways 53 . A key example of the utility of Ssa1 cysteine signaling is the transient activation of the HSR upon treatment with alkylating or oxidizing agents.…”
Section: Discussionmentioning
confidence: 99%